(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this paper was synthesis of TiO2 nanoparticles from TIP in ethanol solution . TiO2 was prepared is anatase from structure and information product from XRD and SEM . TiO2 nanoparticles was prepared study structure and morphology for different thickens 50,80 and 130 nm